العلاقة بين السّلطتين التنفيذية و التشريعية في ظل النظام السّياسي الأمريكي - علي الجنابيّ, كاظم; مجيد العكيليّ, علي (جامعة الوادي University of Eloued, 2016)
الواقع أن النظام الرئاسي، وما يترتب على الأخذ به من إعطاء اختصاصات واسعة وسلطات لرئيس الجمهورية، مما لا يكون لمثله في الدول ذات الأنظمة السياسية الأخرى، قد يثير الخوف في أكثر من الأحيان من أن يصير دكتاتوراً لا تقف إمامه الحدود حائلاً دون الممارسات الإنسانية وإعمال الاعتداء على الحريات البشرية والحقوق المختلفة . كذالك اثبت الواقع العملي في الولايات المتحدة مدى قوة الكونكرس الأمريكي المتمثل في مجلس النواب والشيوخ في مواجهة الرئيس بالنسبة لكافة شؤون الدولة الفيدرالية والمسائل التي تبلغ قدرا معينا من الأهمية، مما حدى بالبعض إلى القول بأن طبيعة النظام الأمريكي تجعله يوصف بأنه حكومة قضاء. كما أن المبدأ العام في النظام الرئاسي يتطلب ابتعاد كل من السلطتين التشريعية والتنفيذية عن بعضهما بمسافة تجعل الفصل الجامد بين السلطتين ممكناً وموجوداً، وبمراجعة نصوص الدستور الأمريكي لعام 1787 ورغم اعتناقه للنظام الرئاسي، إلا انه قرر في كثير من جوانبه إيجاد نوع من العلاقة بين السلطتين لا يصل مداها إلى الحد المقرر في النظام البرلماني، وإنما لإيجاد نوع من التوازن بحيث لا تطغى إحداهما على الأخرى، وبما يعرف بمبدأ الضوابط والتوازنات. Abstract: Indeed, the presidential system and what may result in from it to give more wide specializations and powers to the president, thus, it may not the case with other countries of political regimes, so it may usually raise fear to be a dictator with no boundaries or hails for fulfilling humanitarian practices and acts of violating the human freedom and different rights. The reality in the United States has proved the force of the US Congress of the House of Representatives and the Senate in facing the president for all the affairs of federal state and issues that reach a certain amount of importance, prompting some to say that the nature of the American system is described as the government spend The general principle in the presidential system requires a keeping away of the legislative and executive authorities from each other with a distance that makes a rigid separation between the two authorities possible and existing. With the review of the provisions of the US Constitution in 1787 and, despite of holding the presidential system, but it decided in many of its aspects to find some kind of relationship between the two authorities which did not get range to the limit set in the parliamentary system, but rather to find an equilibrium so that no one overshadows over the other, and what is known as the principle of checks and balances.
Keywords: النظام الرئاسي؛ رئيس الجمهوريّة؛ الكونكرس الأمريكي؛ مجلس النواب؛ مجلس الشيوخ؛ الدولة الفيدرالية